Islam and the Struggle over Political Legitimacy in Egypt: The 1987 Elections through the Lenses of al-Liwa’ al-Islami and Liwa’ al-Islam (Global Media Journal - German Edition, 2020)
The 1987 parliamentary elections in Egypt, held at a time of Islamization and relative political liberalization, resulted in a significant number of seats for the Muslim Brotherhood. Consequently, the political cards were shuffled and the regime and the Brotherhood became involved in a struggle over legitimacy, in which Islam played a central part. Through qualitative content analysis, this paper studies how, in the context of the 1987 elections, Islam was instrumentalized in the struggle over political legitimacy in the governmental journal al -Liwa’ al-Islami and its regime-critical counterpart Liwa’ al-Islam, the latter of which was launched ten days after the first session of Parliament was held. Although the two journals performed different roles, there were many similarities in how both viewed political Islam. I argue that these shared Islamic values functioned as an instrument to connect people and added to the legitimacy of both the regime and the Brotherhood.
Keywords: Muslim Brotherhood; Mubarak; Egypt; legitimacy; political Islam